2005
DOI: 10.1038/nm1264
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and potent DNA vaccination strategy defined by in vivo monitoring of antigen expression

Abstract: Induction of immunity after DNA vaccination is generally considered a slow process. Here we show that DNA delivery to the skin results in a highly transient pulse of antigen expression. Based on this information, we developed a new rapid and potent intradermal DNA vaccination method. By short-interval intradermal DNA delivery, robust T-cell responses, of a magnitude sufficient to reject established subcutaneous tumors, are generated within 12 d. Moreover, this vaccination strategy confers protecting humoral im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
139
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(151 citation statements)
references
References 20 publications
10
139
0
2
Order By: Relevance
“…For this reason, to examine whether hollow microneedle-mediated immunization with PLGA nanoparticles encapsulated OVA may prime OVA-specific endogenous CD8 + T cells in mice, a priming procedure was used consisting of three immunizations delivered over a time period of 6 days. This protocol had been shown to induce cellular immune responses following dermal DNA tattoo immunization [26,42], but not yet when using hollow microneedles [7]. We report here that this prime boost protocol indeed elicits vigorous CD8 + T cell responses in mice immunized with PLGA encapsulated antigen, when using hollow microneedles as delivery method.…”
Section: Discussionmentioning
confidence: 70%
“…For this reason, to examine whether hollow microneedle-mediated immunization with PLGA nanoparticles encapsulated OVA may prime OVA-specific endogenous CD8 + T cells in mice, a priming procedure was used consisting of three immunizations delivered over a time period of 6 days. This protocol had been shown to induce cellular immune responses following dermal DNA tattoo immunization [26,42], but not yet when using hollow microneedles [7]. We report here that this prime boost protocol indeed elicits vigorous CD8 + T cell responses in mice immunized with PLGA encapsulated antigen, when using hollow microneedles as delivery method.…”
Section: Discussionmentioning
confidence: 70%
“…Another method that targets cutaneous DCs is the tattooing of DNA. 18,29,31 Using a relatively low amount of DNA (30 mg), tattooing induces strong cellular and humoral responses against antigens driven by ubiquitous promoters like pCMV.…”
Section: Resultsmentioning
confidence: 99%
“…This technique of dermal DNA vaccination has been previously described. 29 DNA vaccinations were performed with 15 mg of pCMV/EGFP as irrelevant DNA, 15 mg of pCMV/OVA or 30 mg of pDC-STAMP/OVA. At day 8, 15 000 OVA-transfected B16OVA tumor cells were injected subcutaneously into the left flank.…”
Section: Transcriptional Targeting Of Dendritic Cells V Moulin Et Almentioning
confidence: 99%
“…The excellent immunogenicity of dermal DNA vaccination is probably related to the high prevalence of antigen-presenting cells (APCs) in the skin, in the form of Langerhans cells (LCs) in the epidermis and dendritic cells in the dermis (Kanitakis, 2002;Mathers and Larregina, 2006). Several techniques have been developed for the intradermal administration and cellular uptake of naked DNA, such as gene gun and particle injection systems (Klinman et al, 1998;Mitragotri, 2005;Steitz et al, 2006); jet injectors (Mitragotri, 2005;Bahloul et al, 2006); electroporators (Maruyama et al, 2001;Heller et al, 2007;Hooper et al, 2007;Hirao et al, 2008); and a technique, developed at our institute, that has been called ''DNA tattooing'' (Bins et al, 2005;Pokorna et al, 2008). DNA tattooing delivers naked plasmid DNA into the skin through thousands of punctures made with a multiple-needle tattoo device.…”
mentioning
confidence: 99%
“…We have demonstrated that DNA tattooing results in local transfection and expression of the encoded antigen by cells in murine skin. More importantly, the efficacy of DNA tattooing in inducing strong vaccine-specific immune responses has been established in murine models (Bins et al, 2005) and the superiority of DNA tattooing over intramuscular DNA vaccination has been demonstrated in nonhuman primates (Verstrepen et al, 2008).…”
mentioning
confidence: 99%